Pengaruh Social Media Marketing Instagram, Perceived Price, dan Hedonic Motivation terhadap Minat Beli di Yellowfitkitchen pada Masa Pandemi Covid-19 - Willy Sandi; Triyono Arief Wahyudi (UNIVERSITAS KALBIS, 2022)
this research aims to show the influence of Social Media Marketing Instagram, Perceived Price, and Hedonic Motivation on YellowFitKitchen Purchase Intention. There are four variables in this research including Social Media Marketing Instagram, Perceived Price, Hedonic Motivation and Purchase Intention. The researchist used quantitative methods and the sample used in this research amounted 110 respondents who know the product of YellowFitKitchen. The technique used in this research is purposive sampling which is part of non-probability sampling. The research data is analyzed with SPSS 25 shows that Social Media Marketing Instagram Variable have an influence on Purchase Intention, Perceived Price does not have an influence on Purchase Intention and Hedonic Motivation have an influence on Purchase Intention. Social Media Marketing Instagram, Perceived Price, dan Hedonic Motivation Variabels as together have an influence on Purchase Intention.